Analisis Akuntabilitas Pengelolaan Keuangan Dana Desa - Ni Putu Nari Wahyuni; Cokorde Gde Bayu Putra (Hita Akuntansi dan Keuangan, 2023)
The aim of this research was to evaluate the level of accountability in managing village funds in Baha Village, Mengwi District, Badung District during the year 2019. The data analysis technique of qualitative data analysis used by researchers began with the study of all available data from various sources. interviewing, documentation, data reduction, unit compilation, classification, and finally data interpretation. The investigation found that the financial management of the Village Fund conducted by the Baha Village Government complies with the Minister of Home Affairs Regulation No. 20 of 2018 on Village Financial Management. In addition, the Village Fund's financial management process involves the community from the planning stage through oversight. Regarding the report of the village fund by the Baha village government, it is good that it is timely. Reporting is done through meetings with the village advisory bodies Camat, Banjar Dinas, Kelian Banjar, and community leaders, and through poster-style information boards outside village government offices. The implementation of accountability for the Village Fund by the Baha Village Government is administratively sound and technically and managerially sound through the use of the village financial system. The Village Advisory Board does its job well in overseeing the financial management of the village.